Nature and significance of the State's criminal law policy - Воробей, Петро Адамович; Воробей, П. А.; Воробей, Петр Адамович; Vorobei, Petro A.; Vorobey, Petro; Фелик, Василь Іванович; Фелик, В. І.; Фелик, Василий Иванович; Felyk, Vasyl I.; Felyk, Vasil; Нєбитов, Андрій Анатолійович; Нєбитов, А. А.; et al. (Editorial Primmate S. A. S., 2021)
The purpose of the article is to analyze the criminal law policy of the State as one of the main elements of the fight against crime. The subject of the study is the criminal law policy of the State. Methodology: dialectical method, monographic method, logical method, comparative method, system and structural method, method of generalization are used in the course of the research. Research results: The essence and significance of the criminal law policy of the State, its role and place in the general system of legal relations are revealed and the importance of such a mechanism at the national level is emphasized. The current state and level of criminal law policy of the State are criticized. Practical implications: The components of criminal law policy and their relationship with other components of public policy in general are studied. The directions of criminal law policy and its levels are revealed. Value / originality: The limited possibility of the law on criminal liability in the system of social control is emphasized. The general purpose of control over the effectiveness of criminal law policy is indicated.

Метою статті є аналіз кримінально-правової політики держави як одиного із основних елементів боротьби із злочинністю. Предмет дослідження: Предметом дослідження є кримінально-правова політики держави. Методологія: У ході дослідження були використані діалектичний метод, монографічний метод, логічний метод, порівняльний метод, системний та структурний метод, метод узагальнення. Результати дослідження: Розкривається сутність і значення кримінально-правової політики держави, роль і місце в загальній системі правовідносин та підкреслюється важливість такого механізму на загальнодержавному рівні. Піддається критиці сучасний стан та рівень кримінально-правової політики держави. Практичні наслідки: Досліджуються складові кримінально правової політики та їх взаємозв’язок з іншими складовими державної політики в цілому. Розкриваються напрями кримінально-правової політики та її рівні. Цінність / оригінальність: Підкреслюється обмежена можливість закону про кримінальну відповідальність в системі соціального контролю. Вказана загальна мета контролю за ефективністю кримінально-правової політики.
Vorobey P. Nature and significance of the State's criminal law policy / P. Vorobey, V. Felyk, A. Niebytov, V. Matviichuk, O. Vorobey // Amazonia Investiga. – Vol. 10. – Iss. 39. – Editorial Primmate S. A. S., 2021. – P. 225-231.
Keywords: criminal law policy; law-making and law-enforcement activity; views; control; subjects of criminal law policy; кримінально-правова політика; правотворча та правоохоронна діяльність; погляди; контроль; суб’єкти кримінально-правової політики; Research Subject Categories::LAW/JURISPRUDENCE